Monetary Overinvestment and The Fall of Asian Tigers - Raihan (Review on Islamic Accounting, 2022)
The author proposes that the Asian financial crisis can be traced back to the Plaza Accord of 1985, an agreement to artificially strengthen the yen and weaken the dollar. Coupled with low interest rates, the arrangement enabled the fabled speculative boom of the 1990s in East Asia. The essay illustrates, using the Austrian overinvestment theory, how financial liberalization undermined by government exchange interventions can lead to devastating consequences. Government interference in the financial sector, either for the purpose of protecting consumers or domestic manufacturers, results in instability in the long-run. Even after sacrificing the broader economy to subsidize a certain group of manufacturers or consumers, the governments and central banks failed to protect these groups they set out to subsidize in the first place